Design and characterisation of jet cold atmospheric pressure plasma and its effect on Escherichia coli, colour, pH, and bioactive compounds of sour cherry juice. (12th July 2021) - Hosseini, Seyed Mehdi; Hosseinzadeh Samani, Bahram; Rostami, Sajad; Lorigooini, Zahra; Gavahian, Mohsen; Barba, Francisco J.
Summary: A new system for cold atmospheric pressure plasma (CAPP) generation was designed and characterised. The effects of voltage (10, 15, 20 kV), frequency (10, 15, 20 kHz), gas flow rate (3, 5, 7 L min −1 ) and percentage of oxygen (0%, 0.5%, 1%) on the plasma jet length (PJL) were investigated. Then, different volumes (5, 10, 15 mL) of sour cherry juice were treated by CAPP to compare their physicochemical properties (colour and pH), Escherichia coli count, and bioactive compounds with samples treated by the conventional process. According to the results, PJL was increased by increasing the voltage and frequency and then remained constant. Also, PJL increases and then decreases by increasing the gas flow rate. Furthermore, CAPP treatment reduced E. coli count but did not alter the colour and pH of samples. Moreover, increasing the voltage, plasma treatment duration, and oxygen percentage enhanced the inactivation of E. coli . The best sterilisation effect was 6‐log cycle decrease in E. coli count which was achieved at a voltage of 19.6 kV, an oxygen concentration of 1%, and a gas flow rate of 4.5 L min −1 . Besides, the total phenol content of juice was 277 GAE/100 g and was changed to 279 and 359 after plasma treatment and conventional process, respectively. Abstract : In this study, to reduce Escherichia coli in cherry juice, a cold atmospheric pressure plasma jet was generated by dielectric barrier discharge method. The AC power supply used is a variable frequency power supply with a voltage range of 0–20 kV and a frequency range of 6 to 20 kHz. Argon gas and oxygen were used to produce plasma. Plasma characterization was performed by spectrometer. The results showed that cold plasma was able to reduce E. coli in cherry juice.